Analisis Kemampuan Berpikir Kritis dalam Pembelajaran Bahasa Indonesia Pada Kurikulum Merdeka Siswa Kelas VIII SMP Negeri 11 Bengkulu Tengah - Halimah, Nayyun; Khermarinah, Khermarinah; Sari, Wenny Aulia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
ABSTRACT This study aims to describe the critical thinking skills and the factors influencing the critical thinking abilities of eighth-grade students at SMP N 11 Bengkulu Tengah in Indonesian language learning, which is implemented within the framework of the Merdeka Curriculum. The research method used in this study is qualitative. Data collection techniques include interviews, observation, and documentation. The results show that the implementation of the Merdeka Curriculum at SMP N 11 Bengkulu Tengah is underway, but students' critical thinking skills are still limited to levels C1 through C4. Although students demonstrate creativity, many still struggle with understanding concepts, which hinders the application of higher-order critical thinking skills. Psychological factors and learning interactions, such as motivation, attitudes, and teaching methods, also influence students' critical thinking abilities in Indonesian language learning. In conclusion, critical thinking skills within the Merdeka Curriculum at SMP N 11 Bengkulu Tengah have been implemented. The thinking processes in the ongoing learning activities have reached levels C1 (Remembering), C2 (Understanding), C3 (Explaining), and C4 (Analyzing). Keywords: Critical Thinking Skills, Merdeka Curriculum, Indonesian Language Learning.